Growth mode study of MgCl2 on Au foil and Si (111) 7x7, under Ultra High Vacuum by XPS - Karakalos, S. (Engineering, Technology & Applied Science Research, 2011)
The growth mode of MgCl2 on Au foil and Si (111) 7x7 reconstructed surface under UHV conditions, was investigated by X-ray Photoelectron Spectroscopy (XPS). Magnesium chloride grows with the Frank-van der Merve, (FM) growth mode on the Au foil. On Si surface there is evidence for the layer by layer growth of MgCl2 but leaving uncovered silicon areas at the first steps of deposition due to the Si (111)7x7 surface roughness.